Comparative observation of anticoagulant effect of simplified-regional citrate and argatroban in patients with hemodialysis at high risk of bleeding - QIU De-jun; LI Xin-lun; GAO Zhuo; HU Rui-hai; SHAN Jing; LUN Li-de (Linchuang shenzangbing zazhi)
Objective To observe the anticoagulant effects of simplified-regional citrate anticoagulation（S-RCA）and small-dose argatroban in patients with maintenance hemodialysis（MHD）at high-risk of bleeding.Methods We selected 32 hemodialysis patients with active bleeding or bleeding tendency from February 2017 to May 2019 in the blood purification center of our hospital,who were randomly divided into S-RCA group（group A）and argatroban group（group B）.For patients in the group A,4% citrate was continuously pumped into the starting end of the in vitro pipeline system till the end of dialysis;citrate was not supplemented in the venous bubble trap and calcium was not added in the venous circuit.Patients in the group B received a small dose(0.69 μg·kg-1 ·min-1)of argatroban that was pumped continuously in front of the filter during the dialysis.Calcium dialysate（1.5 mmol/L）was applied to both groups.We observed dialysis sufficiency,anticoagulation efficacy of the filter and venous bubble trap,activated partial thromboplastin time（APTT）,change of pre-and post-filtration free calcium(iCa2+),and recorded adverse reactions and bleeding events.Results（1）Patients in both of groups successfully completed 4 h hemodialysis.There was no significant difference in dialysis sufficiency（Kt/v）between group A and group B（1.33±0.16 vs 1.26±0.06,P=0.129）.（2）There was no significant difference in the anticoagulation efficiency of the filter between group A and group B（P=0.600）.The anticoagulant efficiency of venous bubble trap in group A was better than that in group B（93.75% vs 56.25%,P=0.037）.（3）The post-HD APTT in group B was significantly longer than that in group A（40.4±8.2 vs 28.8±1.6,P<0.01）.The pre-and post-filtration APTT during 2 h HD and APTT after HD were both longer than those before HD in the group B（40.0±4.8 vs 39.8±7.2,40.4±8.2 vs 30.7±1.8,P<0.01）.The APTT at 1 hour after dialysis in group B was still significantly longer than that before HD（38.8±7.4 vs 30.7±1.8,P=0.003）.（4）In group A,iCa2+ after HD in was slightly higher than that measured before HD（1.13±0.06 vs 1.06±0.10,P=0.012）,but still in the normal range.（5）One patient in group A experienced lip numbness and improved after citrate flow rate adjustment and calcium supplements.One patient in group B had subcutaneous ecchymosis,but improved spontaneously with no newly or exacerbated bleeding.Conclusions For MHD patients at high risk of bleeding,S-RCA is superior to low dose argatroban method and has more advantages than two-stage RCA anticoagulant method.